Predictive factors for immediate continence after radical prostatectomy - Hatiboglu, Gencay; Teber, Dogu; Tichy, Diana; Pahernik, Sascha; Hadaschik, Boris; Nyarangi-Dix, Joanne; Hohenfellner, Markus (World journal of urology, 2016)
To identify predictive factors for immediate continence after radical prostatectomy.
Published online: 20 May 2015
Gesehen am 06.05.2020